The ghost and the christmas spirit eaudiobook - Holmes, Bobbi (Haunting Danielle, 2020)
It's once again Christmastime at Marlow House and the mediums of Beach Drive have all decided to stay in Frederickport for the holiday. Surprises await for them when the true Spirit of Christmas comes for a visit. Do you believe in Santa Claus?